Pengembangan Produk dan Inovasi Produk pada Teh Hijau Cap Pohon Kurma (Studi pada PT Panguji Luhur Utama) - Bambang Purnomo; Bambang Raditya Purnomo (Universitas Proklamasi 45 Yogyakarta, 2017)
This research aims to explain and analyze product development strategy and product innovation of Green Tea Cap Pohon Kurma. The descriptive method with a qualitative approach is a type of research used by researchers. The purpose of this research can be described the actual situation in accordance with reality, digging, and analyzing more deeply related to product development strategy and product innovation by using observation, interview, and documentation in data collection techniques. The results of this study indicate that the process of product development should be done proactively to pay attention to financial performance of company (financial performance) so that what is expected by consumer in market can also fulfill the expectation from shareholders (stockholders).